(untitled) (Research, Society and Development, 2020)
Objective: This theoretical reflection aims to evidence the clinical nursing care and safety of the patient in the administration of medication. Method: Theoretical-reflexive study, from readings and debates pertinent to the discipline Fundamentals and Practices of Clinical Care of Nursing and Health, Master’s level, of the State University of Ceará. Results and discussion: The text was organized in two thematic axes: Clinical nursing care and patient safety and nursing care in the safe administration of drugs. Final Considerations: It is necessary to share the care with the family and patient, because it favors interpersonal relationships, improves quality management, safety promotion, error prevention and quality of the health care process.